A solid–solid phase change filler with enhanced thermal properties for cooling asphalt mastic. (August 2022) - Jia, Meng; Sha, Aimin; Jiang, Wei; Wang, Wentong; Yuan, Dongdong; Li, Jiange; Dai, Jiasheng; Jiao, Wenxiu
Highlights: Thermal properties of a PUSSPCM were improved by adding graphite flakes. Size effect of graphite flakes on phase change properties of PUSSPCMs was clarified. Innovatively use a GPCM as solid–solid phase change filler in asphalt mastics. Effect of the preferable GPCM on rheological properties of asphalt mastics was revealed. The preferable GPCM had potential to cool asphalt mastics in summer. Abstract: The goal of this work is to improve the latent heat storage capacity and the thermal response rate of a polyurethane solid–solid phase change material (PUSSPCM) for evaluating its applicability as an alternative filler to cool an asphalt mastic. For this purpose, graphite/PUSSPCM (GPCM) structures with various mesh values and contents of graphite were synthesized. The latent heat was initially increased and then decreased with the increasing graphite content. By selecting the optimum content, a GPCM with a larger mesh can possess a higher latent heat. The existence of a relatively large content and mesh of graphite could lead to a higher thermal conductivity for GPCM. The latent heat storage capacity and the thermal conductivity of the synthesized GPCM-8000–1 were 23.2 % and 254.7 % higher than those of PUSSPCM, respectively. Meanwhile, the GPCM-8000–1 material configuration with excellent thermal stability at 200 °C can withstand the high-temperature construction environment of asphalt pavement without liquid leakage and decomposition. As a result, it is recommended as a solid–solid phase change filler to fabricate phase change asphalt mastics. The extracted outcomes from the rheological test results show that the high-temperature deformation resistance, low-temperature cracking resistance and fatigue resistance of the phase change asphalt mastics are improved in contrast to the traditional asphalt mastic. Finally, the cooling effect of the phase change asphalt mastics was evaluated, with the maximum cooling amplitude reaching the value of 5.6 °C.